2021
DOI: 10.1016/j.triboint.2020.106570
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Shoe Tread Parameters using FEM

Abstract: Within this paper, a three-dimensional finite element (FE) model of a uniformly loaded, single rubber block, is described and run using loading conditions replicative of a standard slip resistant footwear test. The FE model considers rubber hyperelastic and viscoelastic material properties, obtained using dynamic mechanical analysis. The performance of the FE model was evaluated through analytical compression analysis and experimental contact area testing. The effect of tread grooves was investigated with rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Additionally, climbing shoe soles are less elastic (Young's modulus = approx. 7.33 MPa [34]) than the skin of fingers (Young's modulus = approx. 0.03 MPa [35]).…”
Section: Discussionmentioning
confidence: 93%
“…Additionally, climbing shoe soles are less elastic (Young's modulus = approx. 7.33 MPa [34]) than the skin of fingers (Young's modulus = approx. 0.03 MPa [35]).…”
Section: Discussionmentioning
confidence: 93%
“…Their analysis revealed that prolonged use and running over certain distances lead to reduced heel absorption due to foam wear in this area. Hale et al [78] employed a 3D finite element (FE) model to investigate the friction coefficient during walking, focusing on the influence of sole groove shapes on slip resistance in rubber footwear. Their study demonstrated a significant effect of sole surface and ground interaction on the friction coefficient, suggesting that different groove shapes and materials could further improve slip resistance.…”
Section: Finite Element Analysis (Fea)mentioning
confidence: 99%
“…material choice, [17][18][19] outsole geometry/tread pattern, 17,[20][21][22][23] and hardness. 24,25 Moreover, enginnering tools such as dynamic mechanical analysis, 26,27 surface energy, 28 rubber friction simulation, 29 and finite-element analysis 30 have also been allied to characterize and optimize the tribological aspect of footwear and elastomers. These engineering features and tools might affect the ACOF in various ways, and it is therefore of high importance to test how a specific shoe performs under the various conditions of the test standard, and whether a new shoe design can achieve the EN ISO 20347 certification.…”
Section: Introductionmentioning
confidence: 99%